GLOBAL ENVIRONMENTAL GOVERNANCE AS A REGULATORY AND GUARANTEE CRITERION FOR ENVIRONMENTAL JUSTICE - Garcia, Denise Schmitt Siqueira; Garcia, Heloise Siqueira; Giménez, Andrés Molina (Novos Estudos Jurídicos, 2017)
This article deals with the theme of Global Environmental Governance to the achievement of Environmental Justice, presenting as general objective to analyze the importance of the first in its public, business and civil society spheres for the regulation and guarantee of the second. Noting up at the end that the Environmental Justice, as a common humanitarian problem, presents itself as the main objective of Global Environmental Governance. In the methodology was adopted the inductive method, having been applied the techniques of the referent, category, operational concepts, bibliographical research and file.